The Question of Intelligence in the Philosophy of Artificial Intelligence - A. Harris, Khalif Muammar; Azlan, Muhammad Ikhwan (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
For more than seven decades, the question of whether it is possible to create intelligent machines has become the central debate in the philosophy of Artificial Intelligence. Many AI researchers, such as Simon and Newell (1958), McCarthy (1978), believe that it is possible to create thinking machines. This view apparently is the mainstream in today’s discourse of Artificial General Intelligence (AGI). This study extends the criticisms put forward by Dreyfus (1965), Searle (1980) and Chomsky (2012), who rejected the possibility of creating thinking and conscious machines. The main questions about the definition of intelligence and intellect are expounded especially from the perspective of Islamic tradition. The limitations of modern Western knowledge on the intellect and the reductionist tendency of Western scientists who limit the human mind to physical neurons have brought about confusion on the possibility of modern technology to create machines that are smarter than the smartest human being. To deliberate on this matter, the author refers to the works of scholars in the fields of philosophy and religion who have dealt with the question of human intelligence, culminating in an in-depth account by Muslim philosophers such as al-Ghazali (1058-1111) and al-Attas (born 1931) regarding the nature of human intellect and of knowledge.